2015
DOI: 10.1016/j.agrformet.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns in the sensitivity of burned area to fire-weather: Implications for climate change

Abstract: Fire is an integral Earth system process, playing an important role in the distribution of terrestrial ecosystems and affecting the carbon cycle at the global scale. Fire activity is controlled by a number of biophysical factors, including climate, whose relevance varies across regions and landscapes. In light of the ongoing climate change, understanding the fire-climate relationships is an issue of current interest in order to identify the most vulnerable regions. Building upon recent global observations of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
103
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(143 citation statements)
references
References 67 publications
11
103
1
4
Order By: Relevance
“…) and subsequent increase in severe fire weather (Bedia et al. ), adequate management will be of utmost importance to ensure the persistence and sustainability of the ecosystem services currently provided by forests. We hope this review will contribute to achieving this goal.…”
Section: Outstanding Knowledge Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…) and subsequent increase in severe fire weather (Bedia et al. ), adequate management will be of utmost importance to ensure the persistence and sustainability of the ecosystem services currently provided by forests. We hope this review will contribute to achieving this goal.…”
Section: Outstanding Knowledge Gapsmentioning
confidence: 99%
“…, Bedia et al. ). While Mediterranean environments are characterized by a summer drought (e.g., period of limited rainfall and high evaporative demand), IPCC (Intergovenmental Panel on Climate Change) predictions forecast an increase in the duration and intensity of the summer drought (IPCC ), which could lead to extreme water scarcity, eventually enhancing tree mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The most active world fire areas (Africa and Latin America) still require modelling efforts. We found that few studies have focused on these most active fire regions largely ignored by research (Chuvieco et al 2008;Krawchuk et al 2009;Knorr et al 2014;Bedia et al 2015), where wildfire databases are not even available (FAO 2010). Improving global wildfire databases in terms of fire location and causes of ignition is essential to have a global diagnosis of HCF occurrence around the world.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…However, undetected, unreported or missing fires are a common problem in many countries, because of a lack of managerial resources and peak fire loads, differing policies on minimum reporting of fire size or fire start location in remote underpopulated regions with low values at risk (Lefort et al 2004). When field-collected fire records are unavailable, fire occurrence can be estimated from remote sensing sources such as burned area products or hotspots (Venevsky et al 2002;Vadrevu et al 2006;Maingi and Henry 2007;Chuvieco et al 2008;Garcia-Gonzalo et al 2012;Marques et al 2012;Zhang et al 2013;Li et al 2014;Bedia et al 2015;Ancog et al 2016). All models built from remote sensing data have had to consider a certain minimum fire size because of technical limitations in sensor spatial or spectral resolution, including, for example, fires .400 ha (Preisler and Westerling 2007;West et al 2016), fires .0.25 ha (Stolle et al 2003) or fires .0.1 ha (Miranda et al 2012).…”
Section: Sources Of Ignition Datamentioning
confidence: 99%
“…The MODIS images are geotagged and corrected for atmospheric effects, such as aerosols and clouds, and are distributed for free. Its products are commonly used for the detection of anthropogenic and natural changes in land cover and vegetation cover phenology (Bedia et al ., ; Fajardo & Gundale, ) and monitoring of spatio‐temporal dynamics of biomes (Adami et al ., ). Other MODIS sensor applications include the detection of fires (Yebra et al ., ; Huesca et al ., ), dynamic monitoring of rivers (Cerdà & Lasanta, ; Keesstra et al ., ), the estimation of biophysical properties of the Earth's surface (Wang et al ., ) and the land use and occupation (Table ).…”
Section: Introductionmentioning
confidence: 99%